2021
DOI: 10.3390/rs13020221
|View full text |Cite
|
Sign up to set email alerts
|

Satellite-Based Precipitation Datasets Evaluation Using Gauge Observation and Hydrological Modeling in a Typical Arid Land Watershed of Central Asia

Abstract: Hydrological modeling has always been a challenge in the data-scarce watershed, especially in the areas with complex terrain conditions like the inland river basin in Central Asia. Taking Bosten Lake Basin in Northwest China as an example, the accuracy and the hydrological applicability of satellite-based precipitation datasets were evaluated. The gauge-adjusted version of six widely used datasets was adopted; namely, Precipitation Estimation from Remotely Sensed Information using Artificial Neural Networks–Cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(13 citation statements)
references
References 69 publications
0
12
0
1
Order By: Relevance
“…CFSR, ERA5, CHIRPS, MERRA2 and PERSIANN-CDR) is used to assess the hydrologic performance of each precipitation product. Some studies showed an improved performance of hydrological models when satellite-based precipitation datasets are employed for calibration (Bitew et al 2012;Peng et al 2021).…”
Section: Model Calibration and Validationmentioning
confidence: 99%
“…CFSR, ERA5, CHIRPS, MERRA2 and PERSIANN-CDR) is used to assess the hydrologic performance of each precipitation product. Some studies showed an improved performance of hydrological models when satellite-based precipitation datasets are employed for calibration (Bitew et al 2012;Peng et al 2021).…”
Section: Model Calibration and Validationmentioning
confidence: 99%
“…In contrast, CHIRPS and ERA5 perform poorly in the daily assessments. Some factors like gauge calibration play a significant role in the performance of SPPs [62]. Therefore, the fact that some products (ARC2, IMERG, PERSIANN, REF2) are gauge calibrated may explain their better performance compared to CHIRPS and ERA5.…”
Section: Discussionmentioning
confidence: 99%
“…Beighley et al [29] evaluated three satellite rainfall products over the Congo Basin via comparison with stream flow and water storage. Peng et al [70] used hydrologic modeling to evaluate satellite rainfall products in an arid region of Central Asia. Additional but non-quantitative checks include examining such variables as cloud cover and surface temperature.…”
Section: Discussionmentioning
confidence: 99%